Web Personalization and Cohort Information Services for Natural Resource Managers - Redman, Crystal (Proceedings of the AAAI Conference on Artificial Intelligence, 2011)
We aim to address yet unanswered questions in web personalization by providing an integrated view of documents found through different tools, considering user confidentiality, emphasizing the benefits of client-side web personalization, and highlighting the power of social webpage recommendation when traditional information retrieval and collaborative filtering methods are used in conjunction. These principles define a framework which leverages groupings of users with overlapping interests called user cohorts.